THE ECONOMIC AND SOCIAL IMPACT OF THE ADOPTION OF VALUE-ADDED TAX IN SAUDI ARABIA - Adel Bogari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The purpose of this study is to determine the economic and social effects of the adoption of value-added tax in the Kingdom of Saudi Arabia. To achieve this goal, a descriptive and an analytical approach was used. We examine a sample of (287) Saudi nationals working in the private and public sectors. Our methodology used the direct questionnaire delivery and receipt method. To process our data and test our research hypotheses, we used SPSS software. The results indicate that the implementation of the value-added tax increases the country’s financial resources. However, such an initiative has a negative social impact and faces many challenges. Bearing on these results, we recommend the need to upgrade the quality of the implementation of the on value-added tax law through improving the efficiency and effectiveness of employees in the General Authority of Zakat & Tax, and simplifying tax procedures until the positive effects on the economic and social side rebound. The researcher recommends the need to overcome economic challenges through the commitment of wholesalers and retailers to release tax invoices for all their dealings, and to organize their businesses through electronic invoices. The researcher recommends the need to overcome the social challenges that face the implementation of the value-added tax law, by promoting trust between the community and the General Authority of Zakat & Tax and activating the role of the Zakat and Tax Authority in spreading awareness and tax culture to the community.